Role of cardiolipin in skeletal muscle function and its therapeutic implications - Youngbum Yoo; MyeongHoon Yeon; Mee-Sup Yoon; Young-Kyo Seo (Cell Communication and Signaling)
Abstract Cardiolipin, a unique phospholipid predominantly present in the inner mitochondrial membrane, is critical for maintaining mitochondrial integrity and function. Its dimeric structure and role in supporting mitochondrial dynamics, energy production, and mitophagy make it indispensable for skeletal muscle health. This review provides a comprehensive overview of cardiolipin biosynthesis, remodeling processes, and essential functions within mitochondria. We explore the influences of cardiolipin on the stability of the mitochondrial complexes, cristae formation, and calcium handling, all of which are vital for efficient oxidative phosphorylation and muscle contraction. Skeletal muscle, with its high energy demands, is particularly dependent on cardiolipin for optimal performance. We discuss the impact of aging on cardiolipin levels, which correlates with a decline in mitochondrial function and muscle mass, contributing to conditions such as sarcopenia. Furthermore, we examined the relationship between cardiolipin and endurance exercise, highlighting the effects of exercise-induced increase in cardiolipin levels on the improvement of mitochondrial function and muscle health. The role of Crls1 in cardiolipin synthesis has been emphasized as a potential therapeutic target for the treatment of sarcopenia. Increasing cardiolipin levels through gene therapy, pharmacological interventions, or specific exercise and nutritional strategies holds promise for mitigating muscle atrophy and promoting muscle regeneration. By focusing on the multifaceted role of cardiolipin in mitochondria and muscle health, we aimed to provide new insights into therapeutic approaches for enhancing muscle function and combating age-related muscle decline. Graphical Abstract Cardiolipin and Crls1 were reduced in aged skeletal muscle, contributing to mitochondrial dysfunction and muscle atrophy. In aged skeletal muscle, reduced CL levels are directly associated with impaired mitochondrial respiration capacity and structural degradation. Upregulating CL synthesis enhances mitochondrial function by stabilizing ETC proteins, increasing oxygen flux, and improving cristae architecture. Therapeutic strategies, including CL-targeting compounds like elamipretide and gene therapy, show promise for mitigating sarcopenia by improving mitochondrial bioenergetics and muscle regeneration.